PERTUMBUHAN DAN HASIL SORGUM PADA PEMBERIAN BEBERAPA DOSIS PUPUK NPK MAJEMUK DI LAHAN PESISIR - Edi Susilo; Hesti Pujiwati; Muhimmatul Husna (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2021)
[GROWTH AND YIELDS OF SORGHUM VARIETIES TREATED WITH VARIOUS DOSES OF NPK FERTILIZER IN COASTAL LAND]. Sorghum has a potential to be developed in marginal land in coastal area. Drought stress and low availability of utrients in the coastal area are the main problems in growing sorghum.  Introducing the drought tolerance variety is one solution to overcome the drought stress in coastal land in order to improve sorghum yields. In addition, the treatment of NPK fertilizer is needed to fulfill the nutrients requirements for growth and yields. This research aims to determine the best sorghum variety and an appropriate dose of NPK fertilizer for the growing sorghum in coastal land. Field experiment was conducted at the coastal area in Bengkulu City from August until November 2021. The experiment was arranged in Randomized Completely Blok Design with two factors. That were sorghum varieties (Numbu, Super 2 and Kawali) and NPK fertilizer doses (150 kg/ha, 300 kg/ha and 450 kg/ha). The results showed that the interaction between sorghum variety and NPK fertilizer dose were not significant on the growth and sorghum yields. Numbu varieties produced the highest panicle weight per plant of 69.42 gram. The research concluded that Numbu variety showed the best growth and yields compare two other varieties. The  maximum growth and yield  of sorghum in coastal land were observed at NPK 450 kg/ha dose.